Dancing with the Tides: Traversing the Academic-Life Balance of Student-Teachers Towards Single Motherhood and Parenting Pariahs - Monina S. Romero (CV. Samuel Manurung and Co, 2024)
Preparing student-teachers to become globally competitive, productive and resilient K-12 educators in the future was a herculean task. Adding pressure to their academic life was the reality that some simultaneously performed various roles and responsibilities. With that insight, the primordial intention of the study is to explore the lived experiences of student-teachers regarding the academic-life balance in single motherhood and parenting pariahs as a baseline for the development of a model for a well-balanced life for student-teachers. The study utilizes the phenomenological design of qualitative research, specifically the DPA (Descriptive Phenomenological Analysis) to six female student-teachers who are selected using the stratified sampling technique from the College of Education (COEd) of the BPSU-Balanga Campus, Philippines. The qualitative data are gathered using the semi-structured interview guide wherein the data are treated using the DPA model proposed by Edmund Husserl. Results indicate that first-time teenage parents face diverse challenges, adapting to parenthood while temporarily adjusting educational and career goals. The pandemic accentuates economic instability, diverse income sources, homeschooling struggles, difficult decisions, and mental health impacts.